1988
DOI: 10.1002/1097-0142(19881101)62:9<2042::aid-cncr2820620928>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis and clinical significance of cytologically detectable oralCandida in acute leukemia

Abstract: Using serial examination and oral cytology, 50 adult patients undergoing induction therapy for acute leukemia were studied for oral colonization with candida species. Ninety percent of patients were found to be colonized with Candida, with most of these colonizations present by day 14. The 30 patients exhibiting colonization with pseudohyphae received ketoconazole 400 mg daily by mouth. Of 20 patients in this group treated for 5 or more days, Candida organisms were eradicated in nine. Sixteen patients from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Immunosuppressive drugs such as the antineoplastic agents have been shown in several studies to predispose to oral candidiasis by altering the oral flora, disrupting the mucosal surface and altering the character of the saliva. 13 45 46 Other factors are smoking, diabetes, Cushing's syndrome, immunosuppressive conditions such as HIV infection, malignancies such as leukaemia, and nutritional deficienciesvitamin B deficiencies have been particularly implicated. Ninane found that 15%-60% of people with malignancies will develop oral candidiasis while they are immunosuppressed.…”
Section: Systemic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppressive drugs such as the antineoplastic agents have been shown in several studies to predispose to oral candidiasis by altering the oral flora, disrupting the mucosal surface and altering the character of the saliva. 13 45 46 Other factors are smoking, diabetes, Cushing's syndrome, immunosuppressive conditions such as HIV infection, malignancies such as leukaemia, and nutritional deficienciesvitamin B deficiencies have been particularly implicated. Ninane found that 15%-60% of people with malignancies will develop oral candidiasis while they are immunosuppressed.…”
Section: Systemic Factorsmentioning
confidence: 99%
“…In the general population, carriage rates have been reported to range from 20% to 75% 4 without any symptoms. The incidence of C albicans isolated from the oral cavity has been reported to be 45% in neonates, 6 45%-65% of healthy children, 7 30%-45% of healthy adults, 8 9 50%-65% of people who wear removable dentures, 9 65%-88% in those residing in acute and long term care facilities, [9][10][11][12] 90% of patients with acute leukaemia undergoing chemotherapy, 13 and 95% of patients with HIV. 14 C albicans is a normal commensal of the mouth and generally causes no problems in healthy people.…”
mentioning
confidence: 99%
“…This highlights the role of the innate defense also in tissues with a negligible adaptive immune cell presence . Many published papers about antifungal peptides describe investigations directed toward oral candidiasis caused by Candida albicans , which is a major human pathogen often associated with serious conditions such as leukemia and HIV/AIDS . Candida species are also among the most frequent nosocomial pathogens leading to bloodstream infections, and they contribute significantly to mortality rates .…”
Section: Introductionmentioning
confidence: 99%
“…(1) It was found that Candida albicans isisolated from the oral cavity of 45% neonates, 45%-65% of healthy children, 30%-45% of healthy adults,50%-65% of people who wear removable dentures, 65%-88% of people those are under acute and long term care facilities, 90% of patients with acute leukaemia undergoing chemotherapy, and 95% of HIV patients. (2)(3)(4)(5)(6)(7)(8) Candida albicans causes 4 th most common nosocomial infection with mortality rate of 39% in year 1995 and it is 3 rd most common nosocomial infection in ICUs with mortality rate of 47%. (9) …”
Section: Introductionmentioning
confidence: 99%